The Effect of Oil and Filer Contents on the Porosity of Lead Acid Battery Separators Produced From Polyethylene - Mohammed, Dr. Malek Mostafa; a Zair, Zyad Rafa’ (Al-Khwarizmi Engineering Journal, 2017)
In this investigation a high density polyethylene (HDPE) was used as a substitute to polyvinylchloride in the production of lead acid battery separators. This has been achieved by preparing mixtures of different percentages of the feed materials which include a high density polyethylene (HDPE) locally produced, filler materials such as silica and oils such as dioctylphthalate (DOP) or paraffin which were added to the mixture to improve the final properties of the separator. The materials were compounded by two roll-mills under the same conditions. The following parameters are involved: 1- Studying the use of a high density polyethylene as a binder to film components with (15-30) wt.%. 2- Studying the use of finely divided silica sand with (25-45) wt.% as a medium to oil adsorption. 3- Studying the use of two type plasticizers (Paraffin or DOP) with (35-55) wt. %. as a creative medium to films porosity. The best results of the feed materials in the mixture were selected so as to give the highest porosity using 15 wt. % PE, 30 wt. % filler, and 55 wt. % oil. It has been found that the films with DOP oil give higher porosity.